2012
DOI: 10.1007/s11668-012-9594-9
|View full text |Cite
|
Sign up to set email alerts
|

Fracture Failure Analysis of a 30CrMnSiA Steel Shaft

Abstract: A shaft suddenly suffered fracture during the test of loading in three directions. The shaft was made from 30CrMnSiA steel. The failure cause was analyzed by visual, stereo, and scanning electron microscopic observations of appearance and fracture surface of the shaft, micro-area composition inspection, metallographic examination, and measurement of the hydrogen content. The results showed that the failure mechanism of the shaft was fatigue fracture resulting from hydrogen-induced intergranular microcracks. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…Shaft components are subjected to a variety of processes during machining, so the level of manufacturing process also directly affects the mechanical properties of shafts and indirectly influences the failure behavior of shafts [21][22][23][24][25]. Hou et al [26] analyzed a fractured shaft in a three-way force loading test. The results showed that the failure mechanism of the shaft was fatigue fracture caused by hydrogen-induced intergranular microcracks.…”
Section: Introductionmentioning
confidence: 99%
“…Shaft components are subjected to a variety of processes during machining, so the level of manufacturing process also directly affects the mechanical properties of shafts and indirectly influences the failure behavior of shafts [21][22][23][24][25]. Hou et al [26] analyzed a fractured shaft in a three-way force loading test. The results showed that the failure mechanism of the shaft was fatigue fracture caused by hydrogen-induced intergranular microcracks.…”
Section: Introductionmentioning
confidence: 99%
“…Compared with other multiaxial loading paths, there are limited studies on multiaxial asynchronous loadings. A lot of researches on steel materials were focused on the fatigue failure under uniaxial and multiaxial constant amplitude loadings, such as the fatigue failure mechanism of 25CrMo4 (EA4T) steel [ 1 , 2 , 3 ] and 39NiCrMo3 steel [ 4 ], crack initiation mechanism of 25CrMo4 steel [ 5 ] and 30CrMnSiA steel [ 6 , 7 ], short crack growth behavior of 25CrMo4 steel [ 8 ], 42CrMo4 steel [ 9 , 10 , 11 ] and 30CrMnSiA steel [ 6 , 7 ], the influence of chemical composition on crack initiation of 25CrMo4 steel [ 12 ], and the influence of loading paths on fatigue failure of 30CrMnSiA steel [ 13 , 14 , 15 , 16 ], while there are limited studies on the fatigue failure mechanism and influencing factors under multiaxial random fatigue loadings.…”
Section: Introductionmentioning
confidence: 99%